Hubungan Pola Komunikasi Guru dengan Pembelajaran Siswa Berkebutuhan Khusus - M. Rafif Kamil; Tresna Wiwitan (Bandung Conference Series: Public Relations, 2024)
Abstract. Inclusion schools are educational institutions that aim to provide education for all students, including children with special needs or disabilities. The main idea behind inclusive schools is to provide equal rights to all students without discrimination based on differences in abilities, needs and personal characteristics. A teacher must have a communication pattern that is used during learning activities, to convey messages that are easily accepted by all students, including students with special needs in inclusive schools. So this is what made the author conduct research with the title "The Relationship between Teacher Communication Patterns and the Learning of Students with Special Needs in Inclusive Schools". This research aims to find out how teacher communication patterns relate to the learning of students with special needs. The method used in quantitative research with a collerational study approach. The population taken was students with special needs at Ibnu Sina Bandung school, while the sample used total sampling technique.. The population of 13 students with special needs. Data collection techniques include interviews, observations and questionnaire results, with collerational analysis technique, with validity and reliability tested to determine the results of this study. Then this research uses information processing theory as a reference and strengthens this research. The results of the study, namely the Ibnu Sina Bandung inclusive school, show that there is a relationship between primary teacher communication patterns and student learning with special needs of 0, 863 which shows a strong relationship. While the relationship between the teacher's secondary communication patterns and the learning of students with special needs amounted to 0.494 which shows a low relationship. Abstrak. Sekolah inklusi merupakan lembaga pendidikan yang bertujuan untuk memberikan pendidikan bagi seluruh peserta didik, termasuk anak berkebutuhan khusus atau disabilitas. Gagasan utama di balik sekolah inklusi adalah untuk memberikan hak yang sama kepada semua siswa tanpa adanya diskriminasi atas perbedaan kemampuan, kebutuhuan, dan karakteristik pribadi. Seeorang guru pasti mempunyai pola komunikasi yang digunakan saat kegiatan pembelajaran berlangsung, untuk menyampaikan pesan yang mudah diterima oleh semua siswa termasuk siswa berkebutuhan khusus di sekolah inklusi. Sehingga hal tersebut yang membuat penulis melakukan penelitian dengan judul “ Hubungan Pola Komunikasi Guru Dengan Pembelajaran Siswa Berkebutuhan Khusus Di Sekolah Inklusi”. Penelitian ini bertujuan untuk mengetahui hubungan pola komunikasi guru dengan pembelajaran siswa berkebutuhan khusus. Metode yang digunakan dalam penelitian kuantitatif dengan pendekatan studi kolerasional. Populasi yang diambil adalah siswa-siswi berkebutuhan khusus di sekolah Ibnu Sina Bandung, sedangkan sampel menggunakan teknik total sampling. Populasi menjadi 13 siswa. Teknik pengumpulan data meliputi wawancara, observasi dan hasil kuisioner, dengan teknik analisis data inferesial analisis kolerasional, dengan diuji validalitas reabilitas dan reabilitas untuk mengetahui hasil penelitian ini. Kemudian penelitian ini menggunakan teori pengolahan informasi sebagai rujukan serta memperkuat penelitian ini. Hasil dari penelitian yaitu sekolah inklusi Ibnu Sina Bandung bahwa terdapat hubungan pola komunikasi guru primer dengan pembelajaran siswa berkebutuhan khusus sebesar 0, 863 yang menunjukan memiliki hubungan yang kuat. Sedangkan hubungan pola komunikasi sekunder guru dengan pembelajaran siswa berkebutuhan khusus sebesar sebesar 0,494 yang menunjukan hubungan yang rendah.